2013
DOI: 10.1103/physrevlett.111.035501
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Complex World of Two-Dimensional Ordering with Three Modes

Abstract: The world of two-dimensional crystals is of great significance for the design and study of structural and functional materials with novel properties. Here we examine the mechanisms governing the formation and dynamics of these crystalline or polycrystalline states and their elastic and plastic properties by constructing a generic multi-mode phase field crystal model. Our results demonstrate that a system with three competing length scales can order into all five Bravais lattices, and other more complex structu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
100
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 40 publications
(67 reference statements)
3
100
0
Order By: Relevance
“…[27][28][29][30] This approach has been applied to the modeling of a large variety of elastic and plastic systems from nano to micron length scales. 11,12,[29][30][31][32][33][34][35][36][37][38][39] The results of this work elucidate the influence of overlayer lattice symmetry on the nature of phase transitions between various superstructured phases. Interestingly the results indicate a dramatic difference between the H-H and H-T systems.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…[27][28][29][30] This approach has been applied to the modeling of a large variety of elastic and plastic systems from nano to micron length scales. 11,12,[29][30][31][32][33][34][35][36][37][38][39] The results of this work elucidate the influence of overlayer lattice symmetry on the nature of phase transitions between various superstructured phases. Interestingly the results indicate a dramatic difference between the H-H and H-T systems.…”
Section: Introductionmentioning
confidence: 75%
“…11 For some H-T systems such as graphene or h-BN layers on metallic surfaces, typically the coupling between film and substrate is quite weak and thus the results of this work are relevant to these graphenetype materials at very small V 0 , leading to the emergence of triangular Moiré patterns as observed experimentally. 17,18 To further validate the H-T results particularly those at large V 0 , sample simulations of a three-mode PFC model for honeycomb lattice 36 were also conducted. The outcomes were consistent with the predictions described above in particular the phenomena of transitions among triangular, stripe, and commensurate phases.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that up to three length scales are sufficient to produce all five two-dimensional (2D) Bravais lattices and other ordered phases [15], while interparticle interactions of two length scales can lead to 6 different 2D quasicrystalline orders [11]. One would expect this length-scale factor also plays an important role on the emergence of system chirality.…”
mentioning
confidence: 99%
“…From a geometric perspective, a resonant triad of wave vectors forming a closed loop can form an equilateral, isosceles, scalene, or collinear triangle, and the following point group symmetries can be stabilized by the 3-waves coupling: C 6 , C 4 , D 2 , and C 1 . Which of them is preferred depends on the number and nature of the length scales involved [15]. For example, the chiral symmetry C 1 can emerge when N = 3, i.e., the wave-vector triplet forms a scalene triangle.…”
mentioning
confidence: 99%
See 1 more Smart Citation